A Shared Vision: The importance of Knowledge Exchange through Co-design in Scaling Circular Strategies for Fashion Remanufacture : Case studies from global perspectives - Borcherdt, Miriam; Child, Emmeline (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Overproduction in the fashion industry poses a significant challenge, leading to excessive resource use and rapidly growing textile waste before garments reach consumers. The Circular Economy (CE) is gaining recognition as a means to reduce resource consumption through various strategies integrated into product lifecycles. However, effectively scaling these strategies to achieve tangible impacts remains underdeveloped. This paper draws on research projects that collaborate with industry partners to incorporate remanufacturing into existing supply chains. It highlights the essential knowledge exchange required for implementing circular production methods, aiming to identify strategies necessary for scaling. The paper enhances understanding of how remanufacturing pre-consumer textiles can be integrated into large-scale fashion business settings. Through two practice-based research projects, one with a major fashion brand and the other with a large garment factory, the research investigates how co-designing pilot projects as a form of knowledge exchange can facilitate the scaling of circular strategies in fashion production. These projects are designed to build capacity, enabling the industry partner to develop systems that can expand the implementation of remanufacturing excess stock. While extensive research exists on circular strategies, there is limited understanding of practical implementation and how collaborations between research and industry can foster a knowledge exchange that supports the transition to circularity. The implementation of remanufacturing, like other circular strategies, depends on adapting processes contextually with a clear understanding of the industry’s existing parameters and developing design responses that can effectively maintain value and recirculate garment stock.